Pengaruh Perencanaan Pajak dan Penerapan Good Coorporate Governance terhadap Nilai Perusahaan - Zul Fahnur Zakaria; Rusliyawati, Rusliyawati; Rudi Kurniawan (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The present inquiry investigates the extent to which tax planning and the practice of good corporate governance (GCG) exert an effect on firm value among consumer goods manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2017 and 2024. Tax planning is operationalized through the Effective Tax Rate (ETR) and Book Tax Difference (BTD), whereas GCG is captured through managerial ownership, institutional ownership, and independent commissioners. Firm value is determined using Tobin’s Q ratio as the evaluative benchmarkThe study applies a quantitative approach with multiple linear regression analysis. From an initial 96 observations, 8 were identified as outliers, resulting in a final sample of 88 data points. The results reveal that BTD and the presence of independent commissioners have a significant positive effect on firm value. Conversely, ETR shows a significant negative effect. Managerial and institutional ownership do not significantly influence firm value. These findings suggest that efficient tax planning and robust governance structures—particularly through independent oversight—play a crucial role in enhancing firm value. The study offers practical implications for corporate management and investors in formulating effective tax and governance strategies.